RhoA/Rho-Kinase in the Cardiovascular System - Hiroaki Shimokawa; Shinichiro Sunamura; Kimio Satoh (2016)
Twenty years ago, Rho-kinase was identified as an important downstream effector of the small GTP-binding protein, RhoA. Thereafter, a series of studies demonstrated the important roles of Rho-kinase in the cardiovascular system. The RhoA/Rho-kinase pathway is now widely known to play important roles in many cellular functions, including contraction, motility, proliferation, and apoptosis, and its excessive activity induces oxidative stress and promotes the development of cardiovascular diseases. Furthermore, the important role of Rho-kinase has been demonstrated in the pathogenesis of vasospasm, arteriosclerosis, ischemia/reperfusion injury, hypertension, pulmonary hypertension, and heart failure. Cyclophilin A is secreted by vascular smooth muscle cells and inflammatory cells and activated platelets in a Rho-kinase–dependent manner, playing important roles in a wide range of cardiovascular diseases. Thus, the RhoA/Rho-kinase pathway plays crucial roles under both physiological and pathological conditions and is an important therapeutic target in cardiovascular medicine. Recently, functional differences between ROCK1 and ROCK2 have been reported in vitro. ROCK1 is specifically cleaved by caspase-3, whereas granzyme B cleaves ROCK2. However, limited information is available on the functional differences and interactions between ROCK1 and ROCK2 in the cardiovascular system in vivo. Herein, we will review the recent advances about the importance of RhoA/Rho-kinase in the cardiovascular system.